Smallholder Farmers’ Perceptions and Adaptations to Climate Change and Variability in Kitui County, Kenya - Mutunga, Evelyn. J; Ndungu, Charles. K; Muendo, Patricia (OMICS International, 2017)
The effects of climate change have highly challenged the productivity of the agricultural sector. The increasing temperatures and erratic rains, as well as diseases and pests have significantly reduced crop yields in the arid and semi-arid regions of Kenya. Though climate change has been the talk of the day, many farmers in the grassroots have hardly adopted any response options and have continued to suffer losses from the inherent effects of climate change. The present study sought to assess the perceptions of small scale farmers on climate change in selected villages in Kitui County and identify adaptation measures adopted by the farmers in response to climate change. Descriptive survey design was used. A total of 177 households were randomly selected to constitute the study sample. Data was coded and analyzed using SPSS version 20. The results showed that most farmers had perceived a changing climate with 74% and 100% of the respondents in Kaveta and Mikuyuni villages respectively, reporting an increase in temperature over the years. Regarding precipitation, 100% and 97% of the respondents in Mikuyuni and Kaveta villages respectively, had noticed a decrease in the average annual rainfall over the last two decades. Further, the results indicated that 76% and 88% of the respondents in Kaveta and Mikuyuni villages respectively had adopted various adaptation options in response to the decreasing rainfall and the unpredictable onset of rains. The study established that farmers in drier areas perceived climate change more and had adapted more to climate change and variability as compared to those in wetter areas. More resources in terms of credit facilities, access to climate change information and extension services should be availed to farmers in areas affected more by climate change and variability to increase their resilience
Keywords: Arid and semi-arid lands; Crop yields; Climate change; Drought resistant crops; Perceptions